Optimization of the GSH-Mediated Formation of Mesoporous Silica-Coated Gold Nanoclusters for NIR Light-Triggered Photothermal Applications - Fernandes, Natanael (2021)
Submitted by CORREIA (icorreia@ubi.pt) on 2021-07-30T10:15:17Z No. of bitstreams: 1 2021 Fernandes Nanomaterials.pdf: 3437122 bytes, checksum: 96b3e064e82d4b87487269fb290ff6c4 (MD5)